2017
DOI: 10.1007/s00432-017-2530-3
|View full text |Cite
|
Sign up to set email alerts
|

Drug-eluting bead transarterial chemoembolization in the treatment for unresectable soft tissue sarcoma refractory to systemic chemotherapy: a preliminary evaluation of efficacy and safety

Abstract: Our data showed that DEB-TACE was effective and safe for patients with soft tissue sarcoma. Therefore, DEB-TACE can be considered as an alternative treatment option for unresectable soft tissue sarcoma refractory to conventionally systemic chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…A retrospective study reveals that 10 patients with unresectable sarcoma refractory to systemic chemotherapy receiving DEB-TACE present with a median survival of 21 months, 1- and 2-year OS rate of 90% and 30%, an ORR of 30.0% and a DCR of 70%, and no severe AE is found post-treatment; and the study concludes that DEB-TACE could serve as an optional treatment for unresectable soft tissue sarcoma refractory to conventionally systemic chemotherapy. [ 7 ] In our study, the patients with other cancers presented with an ORR and a DCR both of 80.0%, and a mean OS of 20.3 months, which indicated a satisfactory efficacy of DEB-TACE in these patients. Moreover, the vast majority of the patients with other cancers presented post-embolization syndrome, and only 1 patient had abdominal discomfort post-treatment, which suggested that DEB-TACE might also be tolerable in these patients.…”
Section: Discussionmentioning
confidence: 51%
“…A retrospective study reveals that 10 patients with unresectable sarcoma refractory to systemic chemotherapy receiving DEB-TACE present with a median survival of 21 months, 1- and 2-year OS rate of 90% and 30%, an ORR of 30.0% and a DCR of 70%, and no severe AE is found post-treatment; and the study concludes that DEB-TACE could serve as an optional treatment for unresectable soft tissue sarcoma refractory to conventionally systemic chemotherapy. [ 7 ] In our study, the patients with other cancers presented with an ORR and a DCR both of 80.0%, and a mean OS of 20.3 months, which indicated a satisfactory efficacy of DEB-TACE in these patients. Moreover, the vast majority of the patients with other cancers presented post-embolization syndrome, and only 1 patient had abdominal discomfort post-treatment, which suggested that DEB-TACE might also be tolerable in these patients.…”
Section: Discussionmentioning
confidence: 51%
“…Laboratory data revealed no thrombocytopenia, hyperbilirubinemia, hypoleucocytosis, or failure of hepatic or renal functions. TACE causes postembolization syndrome, with localized pain, fever, vomiting, nausea, and fatigue being the commonest adverse events [21]. In our case, only fever and localized pain were noted after several days of TACE.…”
Section: Discussionmentioning
confidence: 62%
“…For tumor tissues with large vascular invasion, transcatheter arterial chemoembolization can be used to mix lipiodol with antitumor drugs for injection into the tumor tissue through the large blood vessels. This approach results in tumor vascular occlusion and antitumor effects 4547. For tumor tissues without large vascular invasion, the drug can be injected into the tumor tissue through a puncture under the guidance of computed tomography 48,49.…”
Section: Discussionmentioning
confidence: 99%